Techniques for Food Authentication: Trends and Emerging Approaches - Cichna-Markl, Margit; Mafra, Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue of Foods comprises ten research and two review articles, highlighting the recent advances in food authentication and clearly demonstrating that no single method is suitable to cover all aspects of food authenticity.